Effects of β-(1→3,1→6)-d-glucan and density of diets on the blood profiles of immunologically challenged weaned piglets - Saleh, Mayra A. D. [UNESP]; Amorim, Alessandro B.; Grecco, Henrique A. T. [UNESP]; Berto, Dirlei A. [UNESP]; Padovani, Carlos R. [UNESP]; Orsi, Ricardo de O. [UNESP]; Tse, Marcos L. P. [UNESP] (Elsevier B. V., 2015)
An experiment was conducted to evaluate the effects of two levels of the β-(1→3,1→6)-d-glucan (0 and 500ppm) from yeast Saccharomyces cerevisiae and two levels of energy (3300 and 3450kcalMEkg(-1)) on the hematological, immunological and, biochemical profiles of thirty-six 21-days-old weaned piglets, challenged with 150μgkg(-1) of BW lipopolysaccharide (LPS) from Escherichia coli serotype 055:B5. The experimental design was a randomized complete block design in a 2×2 factorial arrangement with nine replicates per treatment and, one animal per experimental unit. The data were analyzed in accordance with the multivariate analysis procedure of SAS and, the treatment means of parametric and non-parametric data were compared by Bonferroni's test (P<0.05) and, by Dunn's test (P<0.05), respectively. The data of the blood profiles of alanine aminotransferase, alkaline phosphatase and, creatinine showed that LPS did not cause kidney or liver damage in the animals. The addition of beta-glucan in the diets did not prove the robustness of its effect and biological relevance when provided with low nutrient-density. However, its addition combined with the high-nutrient-density diets showed less marked hypoglobulinemia in piglets, which may have contributed to the decreasing of the synthesis of inflammatory mediators.
Keywords: Endotoxin; Hematology; Immunomodulation